Effects of A‐site replacement (Sm, Y, and Pr) on catalytic performances of mullite catalysts for NO oxidation. (1st April 2023) - Chen, Lei; Zhang, Chen; Wu, Tiantian; Huang, Boqiang; Zhang, Jinping; Guan, Guowei; Zhang, Zaoxiao; Hou, Xiaoke; Hu, Chao; Lu, Qiang
Graphical abstract: Highlights: Three kinds of Mn-based mullite nanofibers with different A‐sites were synthesized by a facile electrospinning method. A‐site substitution exhibited an important role in the catalytic performance of mullite catalyst. Structure-activity relationships evidenced that surface adsorbed oxygen and reducibility contributed greatly to superior activity of SmMn2 O5 catalyst. Abstract: Mullite was one of the most promising catalysts that used in the selective catalytic oxidation of NO (NO-SCO), and deciphering its intrinsic properties that affect the catalytic performance was a great challenge but critical to the development of mullite catalysts. Herein, a series of Mn-based mullite nanofibers with different A-site cations were synthesized by electrospinning method and used for catalytic NO oxidation. Activity tests showed that SmMn2 O5 exhibited a better NO conversion rate (77.8 %) than those of PrMn2 O5 (63.3 %) and YMn2 O5 (57.5 %) under typical experimental conditions (GHSV = 120 000 h −1, T  = 325 °C). To investigate the factors influencing the catalytic activity, various techniques including XRD, N2 adsorption, SEM, TEM, EDX, XPS, H2 -TPR, and O2 -TPD were employed, and the results showed that abundant surface adsorbed oxygen species and good reducibility contributed greatly to the catalytic performance of SmMn2 O5 . DFT calculations revealed that A-site cation played the decisive role in the Fermi level relative to the Mn 3d -band centre, thus affecting the adsorption and dissociation of O2 molecule. The present synthetic strategy offered a new viable route for the large-scale preparation of metal oxide catalysts with remarkable NO oxidation performance for practical application.